Penerapan Metode Tsukamoto (Logika Fuzzy) Dalam Sistem Pendukung Keputusan Untuk Menentukan Besarnya Gaji Karyawan Pada Hotel Grand Antares - Kando Narodo Silaban (Journal of Informatics, Electrical and Electronics Engineering, 2021)
Each company, agency, organization or business entity will provide a salary as compensation for the work of an employee, in addition to providing basic salary to its employees, each agency provides a bonus in addition to the basic salary to trigger the performance and work productivity of its employees. This is because an employee who receives the bonus must meet certain criteria relating to disciplinary working hours as determined by each agency or company. Data processing has actually been done since ancient times, it's just that the data processing itself is still very simple and can only solve problems such as very simple calculations. The Decision Support System (SPK) which was developed aims to determine the amount of employee salaries at the Grand Antares Hotel. SPK in this case uses Fuzzy Tsukamoto. The number of factors that drive employee salary determination based on position and demand becomes a consideration and constraints for decision makers in making policies to determine the amount of salary to be determined. These factors are: the maximum demand in a certain period and the minimum demand in a certain period.